Epistimologi Hukum Islam Kontemporer: Upaya Mendialogkan Hukum Islam dan Sosial - ., Sutrisno (Postgraduate Programme of UIN Kiai Haji Achmad Siddiq Jember, 2019)
Islamic law, which has long been engaged with the realities of changing times, has demonstrated its capacity to produce legal norms that correspond to social developments through its methodological foundations. This dynamic character is closely related to the role of Islamic legal philosophy, which discusses the methodological frameworks of falsafat al-tashrī‘ and falsafat al-sharī‘ah. These two dimensions reveal the wisdom behind legal enactments (ḥikmat al-tashrī‘), as well as the objectives and underlying rationales of the law (asrār al-aḥkām). The diversity and reform-oriented nature of Islamic intellectual traditions inevitably affect both the methodology and discourse of Islamic law. Therefore, legal reform in Islamic law cannot be separated from broader intellectual reform. This requires careful examination, as not all thinkers place specific emphasis on legal issues. This becomes particularly significant in the field of Muslim family law, where adaptation and even modification of existing theoretical frameworks are necessary to ensure their relevance. In this context, engaging Islamic law in dialogue with social realities is essential in order to construct an ideal and responsive legal system.